Mid-term assessment of subtalar arthroereisis with Talar-Fit implant in pediatric patients with flexible flatfoot and comparing the difference between different sizes and exploring the position of the inserted implant - Xie, Huan-guang; Chen, Li; Geng, Xiang; Wang, Chen; Zhang, Chao; Wang, Xu; Huang, JiaZhang; Ma, Xin (Frontiers in Pediatrics, 2023)
Background: Subtalar arthroereisis(STA) has been increasingly accepted as a solution to manage Pediatric Flexible Flatfoot. However, STA still remains controversial. The purpose of this study was to research the effect of STA with Talar-Fit implant for the treatment of pediatric flexible flatfoot. First, report the mid-term outcomes of STA with Talar-Fit. Second, compare the outcomes between different sizes of implant. Third, discuss the position of implants inserted.Methods: Fifty-seven pediatric flexible flatfoot who underwent STA from January 2014 to December 2021 were retrospectively analyzed. The feet were divided into five groups according to the size of implant: Group 8,9,10,11,12.Clinical function and radiographic measurements were evaluated. And the position of implants insreted were also recorded, inclding angle, depth and distance.The comparison of pre-and post operation was compared by the paired Student's t-test, and the difference among subgroups was compared by the Wilcoxon rank-sum test. P value <0.05 is considered statistically significant.Results: Seventy-seven feet were successfully followed up for 26.8 months on average. The overall AOFAS score significantly improved from 58.6±10.9 to 85.2±8.6 (P < 0.001). And the Meary's angle decreased from 20.3°± 3.6°to 4.5°± 1.3°, the calcaneal pitch angle increased from 14.8°± 1.6°to 23.6°±2.7°(P<0.05), the talar declination angle decreased from 40.2°±2.3°to 25.5°±3.2°(P<0.05), and the medial longitudinal arch angle decreased from 140.1°±2.8°to 121.4°±3.9°(P<0.05). There were no statistically significant differences between subgroups about the final outcomings. The improvements of calcaneal pitch angle, talar declination angle and medial longitudinal arch angle between different groups were significant difference, however the adjusted P-values were all greater than 0.05. The implant were inserted in a mean angle of 89.5°±2.4°, a mean depth of 0.9mm±2.1mm, and a mean distance of 9.9mm±0.9mm. Complications occurred in 8 patients, including 6 cases of the presence of pain and 2 cases of implant dislocation.STA with Talar-Fit showed satisfactory mid-term results. A larger one may demonstrate a superior effect than the small one. The implants were inserted in a similar position, and indicated that the medial edge of the implant may be able to exceed the midline of talus neck.